Geochemistry of volcanogenic clayey marine sediments from the Hazar-Maden Basin (Eastern Turkey) - Akkoca, Dicle Bal; Kurum, Sevcan; Huff, Warren D. (Slovak Acad Sciences Geological Inst, 2013)
The Hazar-Maden Basin sediments were deposited along the southern branch of the Neotethys Ocean margin during Late Maastrichtian-Middle Eocene times. X-ray powder diffraction (XRD), ICP-AES, ICP-MS and scanning electron microscopy (SEM) were performed on samples of the Upper Maastrichtian-Middle Eocene Hazar Group and the Middle Eocene Maden Complex from the Hazar-Maden Basin to investigate the main effects of depositional environmental parameters in three sections belonging to deeper marine (slope), proximal arc volcanic (Mastarhill and Yukaribag sections) and shallow platform marine (Sebken section) settings. Marine sediments contain clay minerals (smectite, smectite/chlorite, chlorite, illite, interstratified illite/smectite, illite/chlorite, palygorskite), clinoptilolite, quartz, feldspar, calcite, dolomite, opal-CT and hematite. The clays are dominated by iron-rich smectites. La, Zr and Th concentrations are high in the shallow marginal Sebken section where the terrestrial detrital contribution is significant, while Sc and Co are more dominant in the deeper marine (slope) Yukaribag section, which is represented by basic-type volcanism and a higher contribution of hydrothermal phases. In a chondrite-normalized REE diagram, the negative Eu anomaly in samples from Sebken, the section which was deposited in a shallow marine environment, is less significant than that of the other two sections indicating the presence of a high terrestrial contribution in that part of the basin. A decrease in LREEN/HREEN and La-N/Yb-N, La-N/Sm-N ratios from Sebken to Mastarhill and the Yukaribag sections indicates deepening of the basin and an increasing contribution of volcanism in that direction.
Keywords: Mastar Mountain; Eastern Turkey; Elazig area; volcanogenic clayey marine sediments; Neotethys Ocean margin; factor analysis